2003
DOI: 10.1128/jvi.77.9.5305-5312.2003
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Cleavage of the Nonstructural Protein NS1 Mediates Replication of Aleutian Mink Disease Parvovirus

Abstract: Virus-induced apoptosis of infected cells can limit both the time and the cellular machinery available for virus replication. Hence, many viruses have evolved strategies to specifically inhibit apoptosis. However, Aleutian mink disease parvovirus (ADV) is the first example of a DNA virus that not only induces apoptosis but also utilizes caspase activity to facilitate virus replication. To determine the function of caspase activity during ADV replication, virus-infected cell lysates or purified ADV proteins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 40 publications
1
52
1
Order By: Relevance
“…Whether TCRV actively exploits the apoptotic processes to support efficient virus replication and/or release and, if so, by which mechanism, also still need to be determined. A positive influence of apoptosis induction in promoting viral growth or viral replication has been observed for many other viruses (Best et al, 2003;Méndez et al, 2004;Olsen et al, 1996;Wurzer et al, 2003). In those cases apoptotic processes help to overcome the host's immune response or facilitate viral entry or release (Amara & Mercer, 2015;Best et al, 2003;Gliedman et al, 1975;Jeurissen et al, 1992;Teodoro & Branton, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether TCRV actively exploits the apoptotic processes to support efficient virus replication and/or release and, if so, by which mechanism, also still need to be determined. A positive influence of apoptosis induction in promoting viral growth or viral replication has been observed for many other viruses (Best et al, 2003;Méndez et al, 2004;Olsen et al, 1996;Wurzer et al, 2003). In those cases apoptotic processes help to overcome the host's immune response or facilitate viral entry or release (Amara & Mercer, 2015;Best et al, 2003;Gliedman et al, 1975;Jeurissen et al, 1992;Teodoro & Branton, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A positive influence of apoptosis induction in promoting viral growth or viral replication has been observed for many other viruses (Best et al, 2003;Méndez et al, 2004;Olsen et al, 1996;Wurzer et al, 2003). In those cases apoptotic processes help to overcome the host's immune response or facilitate viral entry or release (Amara & Mercer, 2015;Best et al, 2003;Gliedman et al, 1975;Jeurissen et al, 1992;Teodoro & Branton, 1997). It is therefore tempting to speculate that the need for apoptosis induction during TCRV infection, but not JUNV infection, may be related to previously reported differences in the budding of these two viruses (Groseth et al, 2010;Wolff et al, 2013b), and particularly the proline-rich domain-independent nature of TCRV budding (Urata et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellmediated processing of viral proteins is also frequent, although they tend to be structural components. However, it was recently reported that the caspase-mediated cleavage of the NS1 nonstructural protein of a parvovirus was actually required for a permissive infection, opening the possibility that the cleavage products of such proteins may have distinct and important functions in the cell (51). Intriguingly, with regard to the Cproteins, the NS1 is the primary protein responsible for cell cytotoxicity and may be directly responsible for the induction of apoptosis (52).…”
Section: Y Protein Expression: Initiation Versus Proteolytic Processimentioning
confidence: 99%
“…However, there are examples of caspase activation promoting virus replication. For example, caspase cleavage of a nonstructural protein stimulates replication of Aleutian mink disease parvovirus in cultured cells (Best et al, 2003). Caspase 3 can also enhance HSV-1 reactivation from latency when latently infected neurons are explanted (Hunsperger & Wilcox, 2003).…”
mentioning
confidence: 99%